PENYALAHGUNAAN DATA PRIBADI SEBAGAI BENTUK KEJAHATAN SEMPURNA DALAM PERSPEKTIF HUKUM SIBER - Sahat Maruli Tua Situmeang (Faculty of Law, Universitas Pattimura, 2021)
This study aims to determine the regulations regarding the legal protection of the use of personal data in an effort to provide legal certainty to the public and the role of law enforcers in preventing criminal acts of misuse of personal data in the future from the perspective of criminal law reform through normative juridical research methods. Based on the results of the research, it shows that in order to create legal certainty, it is necessary to establish a law that regulates specifically, clearly, structured and comprehensively regarding the protection of personal data and harmonizes existing laws and regulations governing personal data protection as well as clear mechanisms related to coordination between enforcers. law. In this regard, the researcher proposes that there should be the formation of norms regulating criminal sanctions in their enforcement as a deterrent effect as well as reconstruction and reformulation of norms in the regulations regarding personal data protection that are currently in effect.